(untitled) (The Pretoria Student Law Review, 2021)
Government of the Republic of South Africa v Grootboom1 (‘Grootboom’) is a landmark judgment for the interpretation of the right of access to adequate housing in South Africa. In this case the Constitutional Court was confronted with the intolerable and exigent housing needs of Ms Irene Grootboom and her fellow respondents in the Wallacedene community. The community had no access to potable water and sanitation services, the municipality did not collect their domestic refuse, and very few of the informal structures had access to electricity.2 Many members of the community applied for access to low-cost subsidised housing from the Oostenberg Municipality and had been in the housing queue for almost seven years. Despite their actions they faced the prospect of enduring these intolerable conditions indefinitely. Since this prospect was unbearable, the respondents moved out of their waterlogged informal settlement onto a vacant, privately-owned property above the flood line where they erected their informal structures.3